Fertility Counseling Pattern over Time in Young Patients with Breast Cancer: A Retrospective Analysis at a Large Comprehensive Cancer Center - Caterina Barbieri; Ottavia Amato; Anna Chiara Cattelan; Loris Marin; Alessandra Andrisani; Carlo Saccardi; Tommaso Giarratano; Giovanni Faggioni; Elisabetta Di Liso; Carlo Alberto Giorgi; Eleonora Mioranza; Cristina Falci; et al. (IMR Press, 2023)
Background: One main issue to be considered in young patients diagnosed with early breast cancer (BC) is the impact of oncological treatments on fertility and future chances of conception. Current guidelines recommend a comprehensive addressing of oncofertility as part of the management of premenopausal BC patients, including counselling on available assisted reproduction technologies and fertility preservation (FP) strategies. The COVID-19 pandemic represented a potential hurdle to the integration of these procedures into clinical practice. This study aims to describe the time-related evolution in addressing oncofertility issues. Methods: This retrospective mono-institutional observational study considered 206 patients who received neoadjuvant chemotherapy, adjuvant chemotherapy (CT) or adjuvant endocrine therapy (ET), diagnosed with breast cancer at the age of 40 or younger in the years 2014-2015 and 2020-2021. Time-related evolution in addressing oncofertility during oncological consultations and adoption of a fertility or ovarian function preservation (OFP) method were analyzed comparing the two different timeframes. Results: Comparing the two cohorts 2014-2015 and 2020-2021, we found a significant difference in the presence of fertility discussion records (37.4% vs 57.9%, p < 0.01), and in the application of OFP/FP techniques (54.5 vs 78.5%, p < 0.01). In the two cohorts there was a significant difference in OFP (57.6% vs 70%, p = 0.03) and FP techniques application rates (5.1% vs 19.6%, p < 0.01). In the study population, age at diagnosis resulted to influence clinicians' approach towards counseling and/or OFP/FP strategies (87.3% in patients <35 years old (yo) vs 56.7% in older patients, p < 0.01). In the 2020-2021 cohort, age resulted less influential in the choice of using an OFP/FP strategy (87% vs 72.1%, p = 0.18). A higher rate of documented fertility discussion and/or OFP/FP techniques application was recorder in patients who had not had children before BC diagnosis (80.6% vs 64.5%, p = 0.02). When considering only the 2020-2021 timeframe, parity no longer significantly affected the prescription of an OFP/FP strategy (80.4% vs 78.3%, p = 0.93). Conclusions: This study on real world data demonstrates the progressive evolution in the way clinicians approach oncofertility issues, showing a greater attention across years, with more BC patients receiving a dedicated counseling, despite the COVID-19 pandemic.